Repayment of the Public Debt — Financial Leeway by Changing the Repayment Plan at the Expense of Future Generations - Michael Broer (Wirtschaftsdienst, 2022)
Abstract The coalition agreement prevents tax increases. However, the federal government needs income for politically desirable projects. For this reason, the government is planning to stretch the re-payment plan for the corona loans. This policy reduces the repayment burden in the present thereby creating financial leeway for spending. If the yields on government bonds rise in the future, the interest burden will increase due to the extension of the repayment period. If the financial leeway is used for investments, future generations will inherit debts and assets. In fact, federal investment spending over the past two years has been 11.3 %. If this rate is also applied to these funds, there would be a heavy burden on the future generation. This would be a violation of inter-temporal equivalence.